Structural and Functional Effect Mechanisms of Extreme Cooling on Hypothalamus Thermoregulatory Centers - Babijchuk, V. G.; Marchenko, V. S.; Babijchuk, G. A.; Marchenko, L. N.; Bondar, T. I. (Problems of Cryobiology and Cryomedicine, 2004)
The authors studied the central structural and functional effect mechanisms of periodic short term organism cooling in cryochamber (-120Â°C). There has been demonstrated a periodic increase of blood brain barrier (BBB) permeability stipulated by a long-term activation of the neuronsâ€™ synaptic apparatus of pre-optic hypothalamus area. There were presented the suppositions on the relation of cryotherapy therapeutic effect with the increase of functional activity in neurotransmitter-cyclic mononucleosides-retrograde messengers (NO, CO) system which effect was unified at the level of cytolemma and receptor-cytoskeleton complex.